Transcranial Doppler Ultrasonography detection on cerebrovascular flow for evaluating neonatal hypoxic-ischemic encephalopathy modeling - Liu, Jin-Xiang; Fang, Chang-Le; Zhang, Kun; Ma, Rui-Fang; Zhou, Hong-Su; Chen, Li; Wang, Qiu-Lin; Lu, Yu-Xuan; Wang, Ting-Hua; Xiong, Liu-Lin (Frontiers in Neuroscience, 2023)
Objective: This study aimed to investigate the feasibility of Transcranial Doppler Ultrasonography (TCD) in evaluating neonatal hypoxic-ischemic encephalopathy (NHIE) modeling through monitoring the alteration of cerebrovascular flow in neonatal hypoxic-ischemic (HI) rats. Methods: Postnatal 7-day-old Sprague Dawley (SD) rats were divided into the control group, HI group, and hypoxia (H) group. TCD was applied to assess the changes of cerebral blood vessels, cerebrovascular flow velocity, and heart rate (HR) in sagittal and coronal sections at 1, 2, 3, and 7 days after the operation. For accuracy, cerebral infarct of rats was examined by 2,3,5-Triphenyl tetrazolium chloride (TTC) staining and Nissl staining to simultaneously verify the establishment of NHIE modeling. Results: Coronal and sagittal TCD scans revealed obvious alteration of cerebrovascular flow in main cerebral vessels. Obvious cerebrovascular back-flow was observed in anterior cerebral artery (ACA), basilar artery (BA), middle cerebral artery (MCA) of HI rats, along with accelerated cerebrovascular flows in the left internal carotid artery (ICA-L) and BA, decreased flows in right internal carotid artery (ICA-R) relative to those in the H and control groups. The alterations of cerebral blood flows in neonatal HI rats indicated successful ligation of right common carotid artery. Besides, TTC staining further validated the cerebral infarct was indeed caused due to ligation-induced insufficient blood supply. Damage to nervous tissues was also revealed by Nissl staining. Conclusions: Cerebral blood flow assessment by TCD in neonatal HI rats contributed to cerebrovascular abnormalities observed in a real-time and non-invasive way. The present study elicits the potentials to utilize TCD as an effective means for monitoring the progression of injury as well as NHIE modeling. The abnormal appearance of cerebral blood flow is also beneficial to the early warning and effective detection in clinical practice.